2015
DOI: 10.1021/am508491v
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential Roles of Silicon and Germanium Phthalocyanines in Planar Heterojunction Organic Photovoltaic Devices and How Pentafluoro Phenoxylation Can Enhance π–π Interactions and Device Performance

Abstract: In this study, we have assessed the potential application of dichloro silicon phthalocyanine (Cl2-SiPc) and dichloro germanium phthalocyanine (Cl2-GePc) in modern planar heterojunction organic photovoltaic (PHJ OPV) devices. We have determined that Cl2-SiPc can act as an electron donating material when paired with C60 and that Cl2-SiPc or Cl2-GePc can also act as an electron acceptor material when paired with pentacene. These two materials enabled the harvesting of triplet energy resulting from the singlet fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 72 publications
4
107
0
Order By: Relevance
“…has introduced the use of phenoxy‐substituted silicon phthalocyanines, which may be synthesized in a straightforward reaction combining Cl 2 ‐SiPc with an excess of a phenol in refluxing chlorobenzene overnight (Scheme iv). This reaction gives the bis(phenoxy) silicon phthalocyanine in yields above 80 % . More recent studies have explored carboxylate‐substituted silicon phthalocyanines, which may be similarly synthesized by mixing Cl 2 ‐SiPc with an excess of a carboxylic acid in refluxing diglyme or toluene, depending on the solubility of the reagent (Scheme v,vi).…”
Section: Silicon Phthalocyaninesmentioning
confidence: 99%
See 1 more Smart Citation
“…has introduced the use of phenoxy‐substituted silicon phthalocyanines, which may be synthesized in a straightforward reaction combining Cl 2 ‐SiPc with an excess of a phenol in refluxing chlorobenzene overnight (Scheme iv). This reaction gives the bis(phenoxy) silicon phthalocyanine in yields above 80 % . More recent studies have explored carboxylate‐substituted silicon phthalocyanines, which may be similarly synthesized by mixing Cl 2 ‐SiPc with an excess of a carboxylic acid in refluxing diglyme or toluene, depending on the solubility of the reagent (Scheme v,vi).…”
Section: Silicon Phthalocyaninesmentioning
confidence: 99%
“…In a preliminary study, Lessard et al . explored the use of dichlorosilicon phthalocyanine (Cl 2 ‐SiPc) and bis(pentafluoro phenoxy)silicon phthalocyanine (F 10 ‐SiPc) as both donors and acceptors in PHJ devices . It was found that despite nearly identical optoelectrical properties, the F 10 ‐SiPc outperformed Cl 2 ‐SiPc both as a donor and as an acceptor, achieving efficiencies up to 0.40 % as an acceptor paired with α‐6T and up to 0.45 % as a donor paired with pentacene.…”
Section: Silicon Phthalocyaninesmentioning
confidence: 99%
“…Recently, SiPcs have attracted significant interest from our group and others for their integration into OPVs, both as an additive in BHJ devices [48][49][50][51] or as an acceptor or donor in either BHJ or PHJ devices [52][53][54]. We reported the use of bis(6-azidohexanoate)silicon phthalocyanine ((HxN 3 ) 2 -SiPc) as the first dual function ternary additive for OPV, which improved the device stability through cross linking while simultaneously increasing the PCE by absorbing in the near IR region [49].…”
Section: Introductionmentioning
confidence: 99%
“…These results further exemplify that the seemingly minor change from chloride to fluoride in the AlPc structure has significant implications in optoelectronic properties and functionality of AlPc in PHJ OPV devices. Lessard et al [14] have assessed the potential application of dichloro silicon phthalocyanine (Cl 2 -SiPc) and dichloro germanium phthalocyanine (Cl 2 -GePc) in modern planar heterojunction organic photovoltaic (PHJ OPV) devices. The results established the potential for the application of SiPc and GePc in PHJ OPV devices.…”
Section: Introductionmentioning
confidence: 99%